VD_FINDINFO HC / 2010 / 171 vom 3. März 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, AVIS DES DÉFAUTS, FRAIS ACCESSOIRES | 257b al. 1 CO, 257b CO, 267a al. 1 CO, 267a CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 13 LTB